English language - Andrew - Johan; Regina Oktavia; Lusiana Batubara; Dwi Ngestiningsih; Innawati Jusup (LPPM Universitas Abdurrab, 2021)
Background: Serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT) are increased in tissue damage. Ashitaba contains many compounds that can reduce serum SGOT and SGPT levels. Objective: This study was proposed to prove that giving Ashitaba extract could reduce serum SGOT and SGPT levels in rats exposed to burn injury. Methods: This study used a posttest only control group design with 20 rats as samples. All research samples were treated with second-degree burns and were divided into 2 different groups, the treatment group (given Ashitaba extract 300 mg /kg BW) and the control group. The blood serum was analyzed for SGOT and SGPT test on the 2nd, 8th, and 14th days. For statistical analysis, the Wilcoxon test used to analyze the levels of serum SGOT and SGPT. Results: There was no significant difference in serum SGOT and SGPT levels between the control and treatment groups on the 2nd, 8th, and 14th days Conclusion: Ashitaba extract could not reduce serum SGOT and SGPT levels in rats exposed to burn injury.